TATA binding protein dynamics within the cellular chromatin landscape - Yearling, Marie N., author; Stargell, Laurie A., advisor; Luger, Karolin, committee member; Nyborg, Jennifer K., committee member; Yao, Tingting, committee member; Slayden, Richard A., committee member (Colorado State University. Libraries, 2013)
RNA polymerase II (RNAPII) is a twelve subunit enzyme that catalyzes messenger (mRNA) in eukaryotic organisms. A number of essential transcription factors associate with RNAPII to form the pre-initiation complex (PIC) at gene promoter regions. TATA binding protein (TBP) is one member of the transcription machinery indispensable for transcription. At some genes, the formation of the PIC correlates strongly with the transcription output (Ptashne, 2005). These genes have a low occupancy of TBP and other PIC components prior to activation. Upon activation, these factors assemble onto the promoter and transcriptional output increases. Genes that become active upon PIC formation are termed recruitment regulated because their transcription is regulated at the level of recruitment of the PIC to the promoter. While recruitment of the PIC is required for transcription, in many cases promoter-occupancy is not correlated with transcription output. Post-recruitment gene regulation has been conserved across evolution from prokaryotes to humans (Choy et al., 1997; Guenther et al., 2007). At these genes, TBP and RNAPII and other transcription-related factors occupy the promoter region regardless of whether transcription is occurring. Upon gene activation, the occupancy increases only slightly when compared to the increase in transcript level. These genes are described as being poised. At poised genes, these transcription proteins constitutively occupy the promoter region, but it is unknown if the promoter interaction is stable or dynamic. One principal objective of my work was to investigate TBP-promoter dynamics at the poised CYC1 gene in yeast. Due to the genetic and biochemical amenability of the yeast system, studies of the transition of poised CYC1 gene to the active form have provided key insights into the sophisticated molecular requirements involved in this post-recruitment process. To describe the dynamics of the transcription complex bound at the CYC1 promoter I developed a TBP exchange assay. The results suggest that the TBP within the RNAPII transcription complex exists in a relatively stable configuration at the poised gene prior to activation. Upon induction, TBP-promoter dynamics increased at the CYC1 gene promoter. Rapid exchange during activated transcription was also observed at other genes, including at recruitment regulated gene promoters. Overall, we found rapid TBP-promoter exchange to be associated with active transcription. From my findings I propose a model where frequently clearing the promoter offers a functional advantage to support activated transcription.